Smoke-free homes in Poland during the COVID-19 pandemic – a nationwide cross-sectional survey - Aurelia Ostrowska; Jarosław Pinkas; Wojciech Giermaziak; Waldemar Wierzba; Mariusz Gujski; Mateusz Jankowski (International Journal of Occupational Medicine and Environmental Health, 2022)
Objectives Secondhand smoke exposure causes serious health problems. Banning smoking in public venues decreases exposure to secondhand smoke. However, the implementation of smoke-free rules in a private setting (including homes) is largely voluntary. This study aimed to assess the prevalence and characteristics of voluntary smoke-free home rules in Poland during the COVID-19 pandemic as well as to identify factors associated with the voluntary implementation of smoking bans at home.